Structure and performance of Ethiopia’s coffee export sector - Minten, Bart; Tamru, Seneshaw; Kuma, Tadesse; Nyarko, Yaw (International Food Policy Research Institute, 2014)
We study the structure and performance of the coffee export sector in Ethiopia, Africa’s most important coffee producer, over the period 2003 to 2013. We find an evolving policy environment leading to structural changes in the export sector, including an elimination of vertical integration for most exporters. Ethiopia’s coffee export earn-ings improved dramatically over this period, i.e. a four-fold real increase. This has mostly been due to increases in international market prices. Quality improved only slightly over time, but the quantity exported increased by 50 percent, seemingly explained by increased domestic supplies as well as reduced local consumption. To further improve export performance, investments to increase the quantities produced and to improve quality are needed, including an increase in washing, certification, and traceability, as these characteristics are shown to be associ-ated with significant quality premiums in international markets.